Effect of training status on fuel selection during submaximal exercise with glucose ingestion - van Loon, L. J.; Jeukendrup, A. E.; Saris, W. H.; Wagenmakers, A. J. (Journal of Applied Physiology, 1999)
In this study, an oral glucose load was enriched with a [U-(13)C]glucose tracer to determine differences in substrate utilization between endurance-trained (T) and untrained (UT) subjects during submaximal exercise at the same relative and absolute workload when glucose is ingested. Six highly trained cyclists/triathletes [maximal workload (Wmax), 400 +/- 9 W] and seven UT subjects (Wmax, 296 +/- 8 W) were studied during 120 min of cycling exercise at 50% Wmax ( approximately 55% maximal O(2) consumption). The T subjects performed a second trial at the mean workload of the UT group (148 +/- 4 W). Before exercise, 8.0 ml/kg of a (13)C-enriched glucose solution (80 g/l) was ingested. During exercise, boluses of 2.0 ml/kg of the same solution were administered every 15 min. Measurements were made in the 90- to 120-min period when a steady state was present in breath (13)CO(2) and plasma glucose (13)C enrichment. Energy expenditure was higher in T than in UT subjects (58 vs. 47 kJ/min, respectively; P < 0.001) at the same relative intensity. This was completely accounted for by an increased fat oxidation (0.57 vs. 0.40 g/min; P < 0.01). At the same absolute intensity, fat oxidation contributed more to energy expenditure in the T compared with the UT group (44 vs. 33%, respectively; P < 0.01). The reduction in carbohydrate oxidation in the T group was explained by a diminished oxidation rate of muscle glycogen (indirectly assessed by using tracer methodology at 0.72 +/- 0.1 and 1.03 +/- 0.1 g/min, respectively; P < 0.01) and liver-derived glucose (0.15 +/- 0.03 and 0.22 +/- 0.02 g/min, respectively; P < 0.05). Exogenous glucose oxidation rates were similar during all trials (+/-0.70 g/min).